Analisis Implementasi Strategi Proses dalam Meningkatkan Kepuasan Pelanggan pada UMKM Bakso Marem Lamongan - Innayatul fitriyah; Ymelda Nofianti Kristina; Jazilatul Mutafawiqoh; Tirta Indra Setiawan; M.Aidil Azdim (CV. ITTC INDONESIA, 2026)
Meatballs (bakso) are one of the most popular traditional foods in Indonesia and are widely consumed by people from various social and economic backgrounds. The increasing demand for meatballs has encouraged the growth of many Micro, Small, and Medium Enterprises (MSMEs) engaged in their production and sale. As competition among businesses continues to intensify, MSMEs are required to develop competitive advantages to sustain and expand their operations. One important strategy is the implementation of an effective and efficient production process that can improve productivity while maintaining product quality.Bakso Marem Lamongan is one of the MSMEs operating in the meatball industry. As customer demand continues to grow, the business faces several operational challenges, including relatively long production times and limited workforce capacity. These issues can reduce production efficiency and hinder the company’s ability to meet increasing customer orders.To address these challenges, Bakso Marem has implemented a more structured and systematic work process. Clear work procedures, better task allocation, and improved production area layout management help streamline workflow, reduce unnecessary delays, and ensure consistency in production activities. As a result, production time has become more efficient, product quality remains consistent, and service performance has improved. These improvements have contributed to higher customer satisfaction, increased customer loyalty, and growth in sales, supporting the long-term development and competitiveness of the business.